2006
DOI: 10.1302/0301-620x.88b12.18132
|View full text |Cite
|
Sign up to set email alerts
|

Topographical variation in glycosaminoglycan content in human articular cartilage

Abstract: The weight-bearing status of articular cartilage has been shown to affect its biochemical composition. We have investigated the topographical variation of sulphated glycosaminoglycan (GAG) relative to the DNA content of the chondrocyte in human distal femoral articular cartilage.Paired specimens of distal femoral articular cartilage, from weight-bearing and nonweight-bearing regions, were obtained from 13 patients undergoing above-knee amputation. After papain enzyme digestion, spectrophotometric GAG and fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 30 publications
6
44
0
1
Order By: Relevance
“…We hypothesized that postoperative protected weightbearing, inflammation, and overall normalization of mechanical load within the joint will affect the biosynthetic activity of chondrocytes [32,42] and thus leads to characteristic changes in the dGEMRIC index at followup visits. Given that the effect of PAO was most pronounced at the superior aspect of the joint, where the mechanical forces are the greatest in patients with AD, indicates that our results may be truly reflecting the cartilage adaption to normalization in mechanical loading [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that postoperative protected weightbearing, inflammation, and overall normalization of mechanical load within the joint will affect the biosynthetic activity of chondrocytes [32,42] and thus leads to characteristic changes in the dGEMRIC index at followup visits. Given that the effect of PAO was most pronounced at the superior aspect of the joint, where the mechanical forces are the greatest in patients with AD, indicates that our results may be truly reflecting the cartilage adaption to normalization in mechanical loading [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the variation in matrix structure, the volume density of chondrocytes and biosynthetic activity varies with the depth of the cartilage [17,34,43]. Many studies have shown that mechanical loading of articular cartilage affects the metabolism of chondrocytes and its biochemical composition [1,32,37]. Both animal and human studies have shown that the GAG content is higher in cartilage that is habitually loaded [19,33] or has a higher level of activity [39], whereas immobilization results in a reversible decrease in cartilage PG content [18,30].…”
Section: Introductionmentioning
confidence: 99%
“…Over the range of micrometers to millimeters, there are topographical differences in cartilage thickness and matrix content across the surface of the joint, which are associated with the level of loading. 12,13 Further, the properties of articular cartilage change with depth from the articular surface, resulting in a zonal structure that is typically divided into three zones: superficial (surface to 10-20% of thickness), middle (20-70%), and deep (70-100%) (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the implanted tissue comes from an area of low load, showing a thin thickness, a different histological structure and, therefore, a lower functional capacity for dealing with charge absorption. The articular cartilage produced by this technique exhibits topographical variations in morphological, biochemical and physical properties (Xia et al, 2002;Rogers et al, 2006). Because the implanted tissue is harvested from a low-weight-bearing area, the cartilage is thinner and differs in histological structure from cartilage from high weight-bearing areas (Fragonas et al, 1998;Gomez et al, 2000).…”
Section: Mosaicplastymentioning
confidence: 99%